L-theanine combined with epigallocatechin gallate to ameliorate alcoholic liver disease in mice by regulating the intestinal flora and activating the PPARα/FABP1/GPX4 pathway to inhibit ferroptosis - Jiayin Fu; Fei Yan; Dong Qu; Longhua Wang; Xiaohua Chen; Guotao Pu; Wei Yin; Ching Yuan Hu (Food Bioscience, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Development of an innovative in-situ solid-state fermentation system based on endophytic fungi and agrifood by-products pigeon pea roots to enhance genistein production - Jin-Xian Fu; Mo-Nan Wen; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Dan Qu (Innovative Food Science & Emerging Technologies, 2026)

Corrigendum to “L-theanine combined with epigallocatechin gallate to ameliorate alcoholic liver disease in mice by regulating the intestinal flora and activating the PPAR/FABP1/GPX4 pathway to inhibit ferroptosis” [Food Bioscience 83 (September 2026) 109552] - Jiayin Fu; Fei Yan; Dong Qu; Longhua Wang; Xiaohua Chen; Guotao Pu; Wei Yin; Ching Yuan Hu (Food Bioscience, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Influence of LED lighting on the cell growth, accumulation of bioactive flavonoids and terpenoids, antioxidant response, and photoreceptor-mediated light signal transduction in Ginkgo biloba L. callus cultures - Qing-Yan Gai; Jiao Jiao; Yu-Jie Fu; Hong-Yan Zhao; Xiao-Qing Wang; Dan Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Research on dynamic intelligent identification of tunnel formation information based on MWD data - Jianning Wang; Yiguo Xue; Kang Fu; Fanmeng Kong; Yan Ai; Jingkai Qu (Bulletin of Engineering Geology and the Environment, 2026)

Deterioration characteristics of red beds lithological interface under water-rock interaction and its influence on tunnel deformation - Jingkai Qu; Yiguo Xue; Fanmeng Kong; Cuiying Zhou; Jianbing Peng; Su Yan; Zhen Liu; Zhuang Ruan; Mingdong Zang; Kang Fu; Bo Wang; Minghao Jia; et al. (International Journal of Rock Mechanics and Mining Sciences, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Regulatory effects of organic compound L-glutamic acid on multi-scale structural characteristics of starch in high-quality wheat under post-anthesis drought stress - Gang Li; Jialian Wei; Kaiyong Fu; Mei Yan; Gelin Liu; Shiya Qu; Chunyan Li; Cheng Li (Carbohydrate Polymers, 2025)

Mitigation of waste sulfur acid in lead smelting: Substance flow analysis of a case study in China - Hao Fu; Wanmiao Chen; Tianjiao Guo; Wenjun Huang; Haomiao Xu; Zan Qu; Naiqiang Yan (Environmental Research, 2025)

Dynamic MoS2 structural evolution for enhanced flue gas mercury adsorption and desorption under SO2-containing conditions - Yiqi Feng; Qinyuan Hong; Mingze Jiao; Hao Fu; Wenjun Huang; Zan Qu; Naiqiang Yan; Haomiao Xu (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Lipidomics reveals relationship between lipid changes and the development of volatile flavor compounds in Chinese bacon during cyclic temperature smoking - Ziyi Hu; Zhaoxia Qu; Enqi He; Huiyu Zou; Zixin Li; Lei Zhou; Aihua Lou; Yan Liu; Haohua Fu; Jie Luo; Wei Quan; Qingwu Shen (Food Bioscience, 2025)

Spotlight on the accumulation of heavy metals in Traditional Chinese medicines: A holistic view of pollution status, removal strategies and prospect - Yan Liu; Kangzhe Fu; Aijing Leng; Lin Zhang; Jialin Qu (Science of The Total Environment, 2024)

“Butterfly-effect” nano-platforms for cascade immune amplification and tumor clearance through multi-modal therapy and immune sensitization - Haoyu Chen; Xiaoying Kong; Jiahui Yan; Tianyi Wang; Yaqian Lv; Fenglang Zhang; Danping Liu; Yingshan Qu; Jun Fu; Wei Han; Jinsheng Shi (Chemical Engineering Journal, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Staphylococcus warneri strain XSB102 exacerbates psoriasis and promotes keratinocyte proliferation in imiquimod-induced psoriasis-like dermatitis mice - Wenhao Si; Min Li; Kuan Wang; Jialin Li; Mengke Xu; Xiaoyue Zhou; Jie Bai; Zhiyuan Qu; Guoyan Song; Xueya Wu; Yuqi Guo; Hua Hu; et al. (Archives of Microbiology, 2024)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

Niche conservatism over deep timescales and diverse niche axes in land vertebrates - Kristen E. Saban; Yan‐Fu Qu; John J. Wiens (Global Ecology and Biogeography, 2023)
Aim There has been considerable interest in niche conservatism, the idea that ecological variables are similar among related species. Much research has focused on climatic niches of recently diverged species, rather than deeper timescales or non‐climatic niche axes. Furthermore, it has been suggested that conservatism disappears over deeper timescales, and is greater in alpha niche traits (like diet and microhabitat) than beta niche variables (like climate). Here, we test these latter two ideas by comparing patterns of phylogenetic conservatism among 10 niche variables across major clades of land vertebrates. Location Global. Time Period Present to 350 million years ago. Major Taxa Studied Tetrapods, including amphibians, mammals, lepidosaurs (including lizards and snakes), turtles, crocodilians and birds. Methods The 10 niche variables included four alpha niche components (diet, diel activity, habitat, body temperature) and six beta niche components (related to climatic temperature and precipitation). We analysed these variables on time‐calibrated phylogenies with similar taxon sampling (~1700 species), using phylogenetic signal (lambda) to estimate conservatism, along with the D statistic and estimates of evolutionary rates. Results Phylogenetic signal was generally strong across all variables, with lambda generally >0.80 (with 1.0 representing maximum signal). Nevertheless, mean phylogenetic signal was lower in beta niche traits than alpha niche traits (based on lambda and especially the D statistic), and alpha niche traits showed significantly slower rates of evolution. Main Conclusions We address two long‐held views in the literature on niche conservatism, rejecting one but supporting the other. We show that phylogenetic signal does not disappear over deep timescales for many important niche variables, even over 350 million years. We also generally support greater conservatism in alpha niche traits than beta niche traits over hundreds of millions of years, a pattern that was previously suggested (but not explicitly tested) based on closely related species.

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Changes of nitrogen and phosphorus removal pattern caused by alternating aerobic/anoxia from the perspective of microbial characteristics - Kai Yao; Xiao Huang; Wenyi Dong; Fupeng Wang; Xueyong Liu; Yu Yan; Yanhui Qu; Yicheng Fu (Environmental Science and Pollution Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Integrated membrane electrochemical reactor-membrane distillation process for enhanced landfill leachate treatment - Zhongsen Yan; Zhengshi Zhu; Haiqing Chang; Gongduan Fan; Qiankun Wang; Xianzhi Fu; Fangshu Qu; Heng Liang (Water Research, 2023)

Analysis of lunar wrinkle ridges regarding the maximum displacement–length scaling relationship and relevant geological factors - Chenfan Li; Bo Li; Xiaohui Fu; Le Qiao; Zongcheng Ling; Jianguo Yan; Shaojie Qu; Shengbo Chen (Icarus, 2023)

Isolation and characterization of maize ZmPP2C26 gene promoter in drought-response - Fengzhong Lu; Kexin Wang; Lamei Yan; Yalin Peng; Jingtao Qu; Jing Wu; Yang Cao; Qingqing Yang; Fengling Fu; Haoqiang Yu (Physiology and Molecular Biology of Plants, 2020)

Microsatellite records for volume 11, issue 3 - Pengfei Hu; Hao-Xiang Liu; Ying Pan; Yan-Fu Qu; Xueqi Tian; Ke-Xin Wang; Yu-Heng Wei; Xue-Ping Wu; Xiumei Xing; Zhengyi Zhang; Pei Zhao; Yu-Tian Zhao; et al. (Conservation Genetics Resources, 2019)

Effect of freeze-thaw cycles on uniaxial mechanical properties of cohesive coarse-grained soils - Yong-long Qu; Guo-liang Chen; Fu-jun Niu; Wan-kui Ni; Yan-hu Mu; Jing Luo (Journal of Mountain Science, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Bufavirus Protoparvovirus in feces of wild rats in China - Shixing Yang; Dawei Liu; Yan Wang; Fanyong Qu; Yilin He; Zixuan Sun; Quan Shen; Wang Li; Xingli Fu; Xutao Deng; Wen Zhang; Eric Delwart (Virus Genes, 2016)

Isolation and characterization of microsatellite markers in the Asiatic water snake (Xenochrophis piscator) - Zong-Shi Zhou; Tian-Long Fu; Chao-Nan Zhu; Shan Sun; Yan-Fu Qu (Conservation Genetics Resources, 2015)

Isolation and characterization of 12 microsatellite loci in the Chinese Cornsnake, Elaphe bimaculata (Colubridae) - Zong-Shi Zhou; Yan-Xia Zhang; Yan-Fu Qu (Conservation Genetics Resources, 2015)

Isolation and characterization of 10 polymorphic microsatellite loci from the Chinese ratsnake (Zaocys dhumnades) - Rong-Fang Wang; Chao-Nan Zhu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Isolation and characterization of microsatellite loci in the Ussuri mamushi (Gloydius ussuriensis) - Rong-Fang Wang; Yan-Qing Wu; Zhe Liu; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Isolation and characterization of microsatellite loci in the endangered Amur ratsnake Elaphe schrenckii (Reptilia; Squamata; Colubridae) from China - Xue-yang Xu; Tian-long Fu; Yan-Fu Qu; Xiao-xiao Zheng; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Re–Os isotope and platinum-group element geochemistry of the Pobei Ni–Cu sulfide-bearing mafic–ultramafic complex in the northeastern part of the Tarim Craton - Sheng-Hong Yang; Mei-Fu Zhou; Peter C. Lightfoot; Ji-Feng Xu; Christina Yan Wang; Chang-Yi Jiang; Wen-Jun Qu (Mineralium Deposita, 2014)

Microsatellite primer development for the king ratsnakes Elaphe carinata (Colubridae) - Yan-Qing Wu; Rong-Fang Wang; Long-Hui Lin; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Preparation and utilization of molecularly imprinted polymer for chlorsulfuron extraction from water, soil, and wheat plant - Xu Wei Fu; Yan Jiao Wu; Jin Rong Qu; Hong Yang (Environmental Monitoring and Assessment, 2012)

Evolution of viviparity in cold-climate lizards: testing the maternal manipulation hypothesis - Hong Li; Yan-Fu Qu; Rui-Bin Hu; Xiang Ji (Evolutionary Ecology, 2009)

Nonlinear continuum of egg size-number trade-offs in a snake: is egg-size variation fitness related? - Xiang Ji; Wei-Guo Du; Yan-Fu Qu; Long-Hui Lin (Oecologia, 2009)

A phylogenetic analysis of laughingthrushes (Timaliidae: Garrulax ) and allies based on mitochondrial and nuclear DNA sequences - Xu Luo; Yan Hua Qu; Lian Xian Han; Shou Hsien Li; Fu Min Lei (Zoologica Scripta, 2009)
The interspecific relationships among extant laughingthrushes have been unclear for a long time and this has resulted in a confusing taxonomic history. Recent advances in molecular methods have greatly improved the resolution of the phylogeny of birds; however, little works has been done on this specific group because of the inaccessibility to many species. This diverse group includes 50 species mostly distributed in South China and South‐east Asia, and were traditionally arranged into the genus Garrulax , for which the non monophyly had been questioned by previous molecular studies. In this study, we infer a phylogeny for 23 Garrulax species and 20 species from close related genera. Mitochondrial data or combined with nuclear sequences both indicate paraphyly of Garrulax , dividing Garrulax species into two groups. Based on these results, we suggest resurrecting the genus name Trochalopteron Blyth, 1843 for one group and retaining Garrulax for the other pending further study. Using dating methods with a secondary calibration point, we develop a profile of the speciation history of laughingthrushes, which suggests that the Hengduan Mountains might not be the centre of origin for these birds as previously suggested.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Postglacial colonization of the Tibetan plateau inferred from the matrilineal genetic structure of the endemic red‐necked snow finch, Pyrgilauda ruficollis - YAN HUA QU; PER G. P. ERICSON; FU MIN LEI; SHOU HSIEN LI (Molecular Ecology, 2005)
Most phylogeographical studies of postglacial colonization focus on high latitude locations in the Northern Hemisphere. Here, we studied the phylogeographical structure of the red‐necked snow finch Pyrgilauda ruficollis , an endemic species of the Tibetan plateau. We analysed 879 base pairs (bp) of the mitochondrial cytochrome b gene and 529 bp of the control region in 41 birds from four regional groups separated by mountain ranges. We detected 34 haplotypes, 31 of which occurred in a single individual and only three of which were shared among sampling sites within regional groups or among regional groups. Haplotype diversity was high ( h = 0.94); nucleotide diversity was low (ð = 0.00415) and genetic differentiation was virtually non‐existent. Analyses of mismatch distributions and geographically nested clades yielded results consistent with contiguous range expansion, and the expansion times were estimated as 0.07–0.19 million years ago (Ma). Our results suggest that P. ruficollis colonized the Tibetan plateau after the extensive glacial period (0.5–0.175 Ma), expanding from the eastern margin towards the inner plateau. Thus, in contrast to many of the postglacial phylogeographical structures known at high latitudes, this colonization occurred without matrilineal population structuring. This might be due to the short glacial cycles typical of the Tibetan plateau, adaptation of P. ruficollis to cold conditions, or refugia and colonized habitat being semicontinuous and thus promoting population mixing.

Priorities for the conservation of avian biodiversity in China based on the distribution patterns of endemic bird genera - Fu-Min Lei; Yan-Hua Qu; Qian-Qian Tang; Shu-Cheng An (Biodiversity and Conservation, 2003)

Conservation on diversity and distribution patterns of endemic birds in China - Fu-Min Lei; Yan-Hua Qu; Jian-Li Lu; Yao Liu; Zuo-Hua Yin (Biodiversity and Conservation, 2003)